Lessons Learned by Rehabilitation Counselors and Physicians in Services to COVID-19 Long-Haulers: A Qualitative Study. (October 2022) - Wong, Jasin; Kudla, Angelika; Pham, Tri; Ezeife, Nnaemezie; Crown, Deborah; Capraro, Pamela; Trierweiler, Robert; Tomazin, Stephanie; Heinemann, Allen W.
Coronavirus disease (COVID-19) may cause long-lasting adverse consequences after acute recovery, including functional limitations and reduced work capacity. Individuals with long-lasting complications of COVID-19 are known as long-haulers. There is a knowledge gap on how COVID-19 complications affect return-to-work (RTW) efforts. We aimed to describe the challenges that long-haulers encounter when returning to work from the perspectives of rehabilitation professionals. In this study, four certified rehabilitation counselors and four rehabilitation physicians in U.S. outpatient rehabilitation centers participated in focus groups. Participants discussed challenges in working with long-haulers, including personal attributes, post–COVID-19 symptoms and complications, uncertain recovery and unpredictable outcomes, limited health care accessibility and support, and unsupportive work environments. Participants provide individualized services to meet long-haulers' diverse needs as they do for all persons with disabilities, although they expressed uncertainty due to the variable disease course and risk of infection. Modifying workplace policies, especially gradual RTW, were frequently mentioned accommodations. The findings highlight the RTW issues of long-haulers. We provide recommendations on increasing awareness of the challenges and job accommodations of long-haulers.